2012
DOI: 10.1093/hmg/dds233
|View full text |Cite
|
Sign up to set email alerts
|

Human ZMPSTE24 disease mutations: residual proteolytic activity correlates with disease severity

Abstract: The zinc metalloprotease ZMPSTE24 plays a critical role in nuclear lamin biology by cleaving the prenylated and carboxylmethylated 15-amino acid tail from the C-terminus of prelamin A to yield mature lamin A. A defect in this proteolytic event, caused by a mutation in the lamin A gene (LMNA) that eliminates the ZMPSTE24 cleavage site, underlies the premature aging disease Hutchinson-Gilford Progeria Syndrome (HGPS). Likewise, mutations in the ZMPSTE24 gene that result in decreased enzyme function cause a spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 57 publications
0
105
0
2
Order By: Relevance
“…Each filter paper was lodged into the neck of a vial containing 10 mL of scintillation fluid (RPI), capped, and allowed to diffuse at room temperature for 3 h. The base-releasable [ 14 C]-methanol was quantified by liquid scintillation counting. Background counts from ste24Δ rce1Δ yeast with empty vector (77) were subtracted from each sample. IC 50 determinations were performed in triplicate and calculated by using GraphPad 4.0.…”
Section: Methodsmentioning
confidence: 99%
“…Each filter paper was lodged into the neck of a vial containing 10 mL of scintillation fluid (RPI), capped, and allowed to diffuse at room temperature for 3 h. The base-releasable [ 14 C]-methanol was quantified by liquid scintillation counting. Background counts from ste24Δ rce1Δ yeast with empty vector (77) were subtracted from each sample. IC 50 determinations were performed in triplicate and calculated by using GraphPad 4.0.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a reduced enzymatic activity for this variant was confirmed by an in vitro essay. 37 It is still not clear if this mutation is acting per se or in combination with other unknown predisposing factors. It would be interesting to clinically investigate the prevalence of metabolic syndrome in heterozygous carriers of other ZMPSTE24 missense mutations.…”
Section: Pathogenicity Of Splice Site Mutationsmentioning
confidence: 99%
“…This was observed in MAD or 'HGPS' patients carrying compound heterozygous loss-of-function and null ZMPSTE24 mutations and recently confirmed with in vitro studies in which enzymatic analyses performed on a series of ZMPSTE24 variants showed that residual proteolytic activity can be correlated with disease severity. 37 A patient carrying a homozygous loss-offunction ZMPSTE24 mutation (c.281C4T, Leu94Pro) belongs to the clinical continuum of this phenotypic group, as the milder phenotype associated with ZMSPTE24 mutations, which correlated to slight prelamin A accumulation. 24 Finally, progeroid disorders caused by ZMPSTE24 recessive mutations are always severe disorders.…”
Section: Pathogenicity Of Splice Site Mutationsmentioning
confidence: 99%
“…For example, restrictive dermopathy patients carry recessive mutations in the ZMPSTE24 gene, which encodes the proteolytic enzyme involved in lamin A maturation (Barrowman, Wiley, Hudon‐Miller, Hrycyna & Michaelis, 2012). Also, in this case, a mouse model replicates the progeroid phenotype of the disease (Osorio, Ugalde, et al., 2011).…”
Section: Introductionmentioning
confidence: 99%